Educação em saúde ao idoso : saberes e fazeres das equipes de saúde da família - Almeida, Anelise Schell (2012)
The increasing aging rate of the population makes we look for alternatives to the improvement and maintaining of the quality of life to elderly people. In public health, health education for the elderly has been the work s focus of the Family Health Teams, with the principle of act on promoting the health of its users. This study aims to know the knowledge and the doings of the Elderly Health Education, conducted by Family Health Teams, in order to obtain subsidies that contribute to the quality of life for seniors. This is an exploratory descriptive study with qualitative approach, with content analysis, based on Minayo (2004). We interviewed the professionals that work as coordinators of the Family Health Teams in a medium-sized city in north of Rio Grande do Sul, Brazil, which has implanted in its territory 12 Family Health Teams. It was noticed in the study that knowledge of health education to the elderly, in the view of most coordinators, passes the idea of educating the elderly, imparting knowledge to those who have not. The word guide as meaning of health education is constant on the statements. Related to the activities of health education for the elderly, in all statements it has been cited team work with them, and also the difficulty in forming and maintaining the groups, making clear the need to bargain with the elderly to participate in the practices called health education. It cited the opportunity to work in health education with visits at their home, where we can observe the family context, and also work with the elderly in the health unit, paying attention and guiding them. The classification for the work of health education for the elderly does not exist in an organized and often way, seeking to read and learn the subject through the manuals of the Ministry of Health In the speeches of professionals is noticed the strong appreciation to the medical professional, both for the elderly, and by the professional team, strengthening into a new model for health reorganizing: the biomedical model. It is necessary and urgent to train health professionals to work with the elderly, so that policies such as health education is validated in practice, overcoming the apparent dichotomy between theory and practice, where many health professionals may be considered holders of knowledge, ordering acts to the elderly, not considering the context in which they live, like the family, social relations, culture, and in particular the enhancement of knowledge and experience of older people in the process of building practices that maintain and improve the quality of life